Inadequate feeding of infant and young children in India: lack of nutritional information or food affordability? - Malhotra, Nisha (Public health nutrition, 2013)
Despite a rapidly growing economy and rising income levels in India, improvements in child malnutrition have lagged. Data from the most recent National Family Health Survey reveal that the infant and young child feeding (IYCF) practices recommended by the WHO and the Indian Government, including the timely introduction of solid food, are not being followed by a majority of mothers in India. It is puzzling that even among rich households children are not being fed adequately. The present study analyses the socioeconomic factors that contribute to this phenomenon, including the role of nutritional information. IYCF practices from the latest National Family Health Survey (2005-2006) were analysed. Multivariate logistic regression analyses were performed to establish the determinants of poor feeding practices. The indicators recommended by the WHO were used to assess the IYCF practices. India. Children (n 9241) aged 6-18 months. Wealth was shown to have only a small effect on feeding practices. For children aged 6-8 months, the mother's wealth status was not found to be a significant determinant of sound feeding practices. Strikingly, nutritional advice on infant feeding practices provided by health professionals (including anganwadi workers) was strongly correlated with improved practices across all age groups. Exposure to the media was also found to be a significant determinant. Providing appropriate information may be a crucial determinant of sound feeding practices. Efforts to eradicate malnutrition should include the broader goals of improving knowledge related to childhood nutrition and IYCF practices.